Kebijakan Hukum Pidana dalam Penanggulangan Tindak Pidana Perdagangan Anak - I Ketut Eka Yoga Juliantika; I Made sepud; I Ketut Sukadana (Jurnal Konstruksi Hukum, 2020)
Children are often victims of child trafficking crime. There are a lot of factors that support the crime of child trafficking, one of which is the lack of regulation on child trafficking. Based on this background, this research was conducted with the aim of describing how the regulation of child trafficking and how the criminal law policy against child trafficking. This research was designed using a normative legal research method. The results of this study indicated that the regulation of child trafficking is regulated in Law No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons, the Criminal Code (KUHP), namely Article 297, Article 301, Article 324, Article 328, and Article 330, RI Law No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons, Law No. 35 of 2014 on Amendments to Law no. 23 of 2002 concerning Child Protection, and Law no. 11 of 2012 concerning the Juvenile Criminal Justice System. Furthermore, the criminal law policy against child trafficking is regulated in the Criminal Code, the Criminal Procedure Code, Law no. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons, Law no. 11 of 2012 concerning the Child Criminal Justice System, and Law no. 35 of 2014 concerning amendments to Law no. 23 of 2002 concerning Child Protection.